1991
DOI: 10.2134/jeq1991.00472425002000010046x
|View full text |Cite
|
Sign up to set email alerts
|

Coal Waste Reclamation using Automated Weathering to Predict Lime Requirement

Abstract: Abandoned coal waste exhibits adverse physical and chemical properties which preclude vegetation establishment. Coal waste from a site in Montana was acidic (pH 2.8), black, 85% coarse fragments and had a low water holding capacity. Incorporation of cement kiln dust (CaO) and limestone (CaCO3) to 35 cm at rates recommended by a weathering procedure neutralized coal waste acidity in the surface 10 cm. Incorporating CaO to 100 cm neutralized coal waste to the 30‐cm depth. Seeded vegetation was healthy and vigoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…These are relatively low values given the lime and topsoil surface treatments employed. This observation is consistent with that of Gitt and Dollhopf (1991) who found that incorporating lime into refuse made no significant change in leachate pH beyond their 20-cm depth of incorporation. Leachate pH was profoundly influenced by the leachate volume or total mass of flow.…”
Section: Treatment Effects On Leachate Qualitysupporting
confidence: 91%
“…These are relatively low values given the lime and topsoil surface treatments employed. This observation is consistent with that of Gitt and Dollhopf (1991) who found that incorporating lime into refuse made no significant change in leachate pH beyond their 20-cm depth of incorporation. Leachate pH was profoundly influenced by the leachate volume or total mass of flow.…”
Section: Treatment Effects On Leachate Qualitysupporting
confidence: 91%
“…It is worth mentioning that Picea abies acidified more of the soil over the years than the other plants. Previous studies show that a mine soil pH usually ranges from 6.0 to 7.5, which is suitable for the growth of forages and other agronomic or horticultural uses [31,32].…”
Section: Soil Phmentioning
confidence: 99%
“…Vegetation achieves optimal growth in soils at neutral pH. A mine soil pH range in the range of 6.0 to 7.5 is ideal for forages and other agronomic or horticultural uses (Gitt and Dollhopf, 1991;Gould et al, 1996). Maiti and Ghose (2005) reported that the pH vary from 4.9 to 5.3 in a mining dump site situated in Central Coalfield Limited's (CCL), North Karanpura area, in the Ranchi district of Jharkhand State of India and thus indicated the acidic nature of the dumps.…”
Section: Soil Phmentioning
confidence: 99%